ANALISIS KEARIFAN LOKAL DI SEKOLAH DALAM MEMBENTUK SIKAP MULTIKULTURAL SISWA SEKOLAH DASAR - Syahla Habibah; Mahmud Yunus; Fitri Novianti Baihaqi; Azahra Dila (LPPM Universitas Cipta Mandiri, 2025)
Multicultural education is crucial for fostering tolerance and harmony amidst Indonesia's cultural diversity. This study examines the integration of local wisdom values in multicultural education in elementary schools and its impact on students' multicultural attitudes. Using a qualitative descriptive method with interviews and observations, the research finds that incorporating local wisdom values such as gotong royong and tolerance cultivates positive character traits in students. The findings suggest that multicultural education based on local wisdom is effective in shaping strong multicultural attitudes and is relevant for education in Indonesia. This study highlights the importance of integrating local wisdom values into school curricula to build a harmonious and character-driven society.